1995
DOI: 10.1091/mbc.6.4.471
|View full text |Cite
|
Sign up to set email alerts
|

The SRP9/14 subunit of the signal recognition particle (SRP) is present in more than 20-fold excess over SRP in primate cells and exists primarily free but also in complex with small cytoplasmic Alu RNAs.

Abstract: The heterodimeric protein SRP9/14 bound to the Alu sequences of SRP RNA is essential for the translational control function of the signal recognition particle (SRP). The Alu RNAs of primate cells are believed to be derived from SRP RNA and have been shown to bind to an SRP14-related protein in vitro. We have used antibodies to characterize SRP9/14 and examine its association with small RNAs in vivo. Although SRP9 proteins are the same size in both rodent and primate cells, SRP14 subunits are generally larger i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 58 publications
(91 reference statements)
7
64
0
Order By: Relevance
“…1a). Each arm is related to the Alu portion of SRP RNA in terms of sequence and secondary structure and can bind the cognate SRP protein SRP9/14 in vitro [11] and in vivo [12,13]. Recent results from our group revealed that synthetic Alu RNPs (ribonucleoproteins), composed of Alu RNA in complex with SRP9/14, and naked Alu RNA have opposite effects on protein synthesis in cell-free translation systems.…”
Section: Free Alu Rnas and Protein Translationmentioning
confidence: 99%
See 3 more Smart Citations
“…1a). Each arm is related to the Alu portion of SRP RNA in terms of sequence and secondary structure and can bind the cognate SRP protein SRP9/14 in vitro [11] and in vivo [12,13]. Recent results from our group revealed that synthetic Alu RNPs (ribonucleoproteins), composed of Alu RNA in complex with SRP9/14, and naked Alu RNA have opposite effects on protein synthesis in cell-free translation systems.…”
Section: Free Alu Rnas and Protein Translationmentioning
confidence: 99%
“…Further investigations of the mechanism by which they influence protein translation showed that both of them act at the level of translation initiation [14]. A large fraction of the protein SRP9/14 is not assembled into SRP in primate cells [12]. The free SRP9/14 may bind Alu RNA and the occurrence of Alu RNP in vivo seems therefore very likely.…”
Section: Free Alu Rnas and Protein Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that SRP9/14 might possess a new RNA binding motif which may be generated upon heterodimerization since neither protein alone binds specifically to SRP RNA. Recently, it has been shown that human SRP9/14 in vivo [7], and SRP14 in vitro [25] can associate as complexes with scAlu RNA in so-called Alu particles. Furthermore, the human SRP14 is larger than its murine counterpart, this difference being due to a C-terminal alanine/threonine-rich extension [25].…”
Section: Introductionmentioning
confidence: 99%